PIROLISIS CAMPURAN BIOMASSA LIMBAH AMPAS KOPI DAN LIMBAH PLASTIK POLYPROPYLENE - Lutfi Ilunsa Zain; Danar Susilo Wijayanto; Taufik Wisnu Saputra (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
The need for energy progressively increase, meanwhile fossil fuel reserves gradually decrease since it is nonrenewable resourses. Coffee grounds and polypropylene plastic waste can be used as alternative fuels. One of the ways to use coffee grounds and plastic waste as fuel is through the pyrolysis process. Pyrolysis is a chemical decomposition process of a material thermally in the absence of oxygen which converts RDF-4 into a liquid smoke product in the form of oil. The purpose of this study was to determine the effect of the comparison of the composition of the mixture of coffee grounds and polypropylene plastic waste on the quantity of pyrolysis oil. This study uses an experimental method with quantitative descriptive analysis techniques. This research was carried out by means of a pyrolysis process on RDF-4 a mixture of coffee grounds biomass waste and polypropylene plastic waste with various composition ratios of 0%:100%, 25%:75%, 50%:50%, 75%:25%, and 100%:0%. The pyrolysis oil is then filtered, for later testing the quantity. The test shows that there is an effect of variations in the ratio of the composition of the biomass mixture to the quantity of pyrolysis oil. RDF-4 from coffee grounds waste mixed with polypropyelene plastic waste produces a quantity that tends to decrease as the ratio of coffee grounds composition decreases. RDF-4 which is not mixed with coffee grounds or has a composition ratio of coffee grounds less than the composition ratio of polypropylene plastic waste produces pyrolysis oil with more quantity and quality that tends to be better than the ratio of other RDF-4 compositions. The quantity of pyrolysis oil produced ranged from 219.33 ml to. 1026.67 ml. RDF-4 from 100% polypropylene plastic waste produces pyrolysis oil with the highest quantity of 1026.67 ml with the highest pyrolysis temperature achieved 391°C at T1, 345.5 °C at T2, and 367.75 °C at T3.